2011
DOI: 10.1186/2229-0443-1-2-7
|View full text |Cite
|
Sign up to set email alerts
|

Application of Structural Equation Modeling in Assessing the Relationship Between Stuttering Students' Cognitive and Metacognitive Strategies and Their Reading Comprehension Performance

Abstract: Language testing is not limited to assessing the performance of ordinary learners. It is also needed in other field such as assessing the ability of children with disabilities, those who have language disorders. Although a great deal of research has been carried out in the realm of stuttering, researchers still do not know why some children stutter, or why most children become fluent speakers while others become adult stutterers. Studies show that Stuttering students have many difficulties in Reading Comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…The third level is the level of the situation model. This level involves combining textual information with schemata or previous knowledge that the reader already has (Ghaemi & Ghaemi, 2011;Mckee, 2012). So it can be concluded that reading comprehension is a constructed mental operation.…”
Section: Level Of Representation and Metacomprehensionmentioning
confidence: 99%
“…The third level is the level of the situation model. This level involves combining textual information with schemata or previous knowledge that the reader already has (Ghaemi & Ghaemi, 2011;Mckee, 2012). So it can be concluded that reading comprehension is a constructed mental operation.…”
Section: Level Of Representation and Metacomprehensionmentioning
confidence: 99%
“…These results indicate that B/C Ratio> 1 and the effort / investment made by the employees is profitable or feasible. [68] states that benefit cost ratio is an assessment carried out to see the efficient level of cost usage in the form of a comparison of the number of positive net present values with a negative net present value (NPV), or in other words, Net B / C is the ratio between the positive NPV and a negative NPV and this shows a description of how many benefits will be obtained from the costs incurred.…”
Section: Benefit and Costs Of Educational Investment (B/c Ratio -Benementioning
confidence: 99%
“…The results revealed that neither cognitive nor metacognitive strategy use had a direct effect on the test performance. Similarly, Ghaemi and Ghaemi (2011) …”
Section: Literature Reviewmentioning
confidence: 99%